Out of reach? Convergence to an inflation target in the Central Bank of Iceland's macroeconomic model - Baldursson, Fridrik M.; Hall, Axel (2008)
Inflation scenarios in forecasts of the Central Bank of Iceland (CBI) appear to converge to the inflation target (2.5%) in 8-9 quarters. We ask whether this is a coincidence or an inherent property of the CBI’s model, QMM. We formulate a sub-model, containing equations for inflation, inflation expectations, wages, exchange rate and the policy interest rate. We find that rapid convergence toward the inflation target is a property of the QMM when a Taylor-rule is included in the model. Underlying is an inflation expectations equation which assumes a high degree of credibility of the CBI. This equation, however, lacks empirical underpinnings. When we replace the QMM expectations equation with an estimated equation, a more realistic picture emerges where the Central Bank has to raise the policy rate considerably higher than in QMM scenarios and it takes much longer to reach the inflation target.